Cause of Death - Cornwell, Patricia (New York G.P. Putnam's Sons, 2006)
An investigative reporter is found dead in Virginia's icy waters ... New Year's Eve and the final murder scene of Virginia's bloodiest year takes Scarpetta thirty feet below the Elizabeth River's icy surface. A diver, Ted Eddings, is dead, an investigative reporter who was a favourite at the Medical Examiner's office. Was Eddings probing the frigid depths of the Inactive Shipyard for a story, or simply diving for sunken trinkets? And why did Scarpetta receive a phone call from someone reporting the death before the police were notified? The case envelops Scarpetta, her niece Lucy, and police captain Pete Marino in a world where both cutting-edge technology and old-fashioned detective work are critical offensive weapons. Together they follow the trail of death to a well of violence as dark and forbidding as water that swirled over Ted Eddings
Keywords: Virginia -- Women detectives -- Forensic pathologists